(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim of study: The aim of this study was to evaluate the etiology, site and severity, main age group effected by maxillofacial injuries and also evaluate different treatment modalities and fallow up to evaluate the result of management protocol.Study design: The sample considered of 116 patients with maxillofacial injuries, main of them treated at maxillofacial department of Al-Hussain teaching hospital and some of them in private hospitals and private clinics, in al Nasiriyah city from October 2019 to April 2021. The referred patients and patients with severe neurological injury were excluded from this study.Result: This study raveled that the zygomatico-maxillary injury is the most site involved followed by mandibular fracture. And the most common causative factor of injury associated with these protests was the two or three wheels’ motor injury followed by direct missile injury. The most acceptable and reliable bone graft was the iliac bone with less complications in donor site. The most common complication was the infection and can be control by antibiotic cover with early wound cleaning protocol as a first step and delayed management protocol as a second step.Conclusion: Rubber bullet injury in maxillofacial region has high risk of ocular damage, and may need major surgical intervention with bone graft reconstruction in case of blow out fracture. Delayed two stages management strategy mostly used in this study and give more acceptable result than early one stage management strategy, but that in associated with our center due to lack of surgical equipment and assistance staff at night. So to compare between two strategies need farther studies.